2006
DOI: 10.1007/s10508-006-9018-6
|View full text |Cite
|
Sign up to set email alerts
|

Grade Failure and Special Education Placement in Sexual Offenders’ Educational Histories

Abstract: A sample of 701 adult men underwent assessment following illegal or clinically significant sexual behaviors or interests. Patients were categorized on the basis of phallometric (penile) responses in the laboratory to erotic stimuli depicting adults, pubescent children, and prepubescent children; histories of sexual offenses; and self-reported sexual interests. Comprising the categories were men sexually interested in prepubescent children (pedophiles; n = 114), men sexually interested in pubescent children (he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
4
27
0
1
Order By: Relevance
“…On the one hand, previous studies using neuropsychological variables like IQ or related variables such as school failure (Cantor et al, 2006) could suggest that hebephiles are intermediate and in some sense''equidistant''from pedophiles and teleiophiles (e.g., Blanchard et al, 2007). On the other hand, children in Tanner Stages 2 and 3-the preferred sexual objects of hebephiles-might be perceived as physically more similar to children in the later years of Tanner Stage 1 than to fully mature individuals (Tanner Stage 5) by the average human observer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, previous studies using neuropsychological variables like IQ or related variables such as school failure (Cantor et al, 2006) could suggest that hebephiles are intermediate and in some sense''equidistant''from pedophiles and teleiophiles (e.g., Blanchard et al, 2007). On the other hand, children in Tanner Stages 2 and 3-the preferred sexual objects of hebephiles-might be perceived as physically more similar to children in the later years of Tanner Stage 1 than to fully mature individuals (Tanner Stage 5) by the average human observer.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of findings suggests that neurodevelopmental perturbations in utero or during early childhood increase the risk of pedophilia (e.g., Cantor, Blanchard, Robichaud, & Christensen, 2005). For several relevant variables, hebephiles have produced means intermediate between those for pedophiles and those for teleiophiles (Blanchard et al, 2003Cantor, Klassen et al, 2005;Cantor et al, 2004Cantor et al, , 2006Cantor et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Paedophilia shows a greater departure from typical than does hebephilia (the erotic interest in pubescent children; Glueck, 1955) or teleiophilia in several other domains, including general intelligence (Cantor, Blanchard, Robichaud, & Christensen, 2005), grade failure and placement in special education classes (Cantor et al, 2006) and differences in self-reported height (Cantor et al, 2007). Therefore, we expected paedophiles would demonstrate higher rates of left-handedness than either of those groups, rather than elevated rates of ambiguous-handedness.…”
mentioning
confidence: 99%
“…Cantor et al, 2006;Connolly & Woollons, 2008;Starzyk & Marshall, 2003)-characteristics which are established risk factors for offending recidivism (Hanson & Harris, 2000;Hanson & Morton-Bourgon, 2005). This suggests that some aspects of Sexual Offender Treatment Programmes (SOTPs) designed for non-MDSO populations may be beneficial for MDSOs.…”
Section: Discussionmentioning
confidence: 99%